Obtención de la función cuadrática de costo de combustible para el despacho económico óptimo de generación en el área de generación a crudo en el Bloque 16 operador por Repsol Ecuador. - Cruz Panchi, Omar Danilo (2020)
Electrical energy is considered as a product or service to supply the demand of its beneficiaries, from the market point of view. Everything starts from the generation of electrical energy and must be of quality, sustainable and efficient; Its technical, physical and electrical factors are part of the energy conversion process and its economic factors in its production stages are part of the generation cost. This work presents the methodology to obtain the functions: characteristic, thermal regime (Heat Rate), generation cost and incremental cost of the thermal generation units. These functions were developed from the conversion of data obtained from field tests, using research instruments such as obtaining information from primary and secondary sources. Seven generating units (Wartsila Vassa 18V32LN Engine – ABB Generator, 13.8 kV) installed in Block 16 were evaluated in the tests.